Considerations of sustainability in capital budgeting decision-making. (20th August 2021) - Frost, Geoffrey; Rooney, James
Abstract: With its focus on financial performance, accounting has played a central role in conceptualizing the success of modern business organisations. This dominant focus, however, can create tension in decision-making when organisations are challenged on sustainability performance. In recognising these limitations, various frameworks or models have been proposed to extend accounting beyond the financial and to integrate sustainability measures and performance. Whilst evidence has been forthcoming on the effective application of these frameworks, there is limited evidence from practice of how the fundamental concepts of these frameworks may shape decision-making. This paper examines the extent to which sustainability is considered in the context of capital budgeting decisions, a core role of management accounting with broadly accepted accounting technologies supporting performance measurement and decision-making. Rather than focusing on a specific formal framework, the paper explores how decisions makers in various contexts may draw upon and adapt concepts identifiable within the various frameworks to address acknowledged limitations with the financial focus of accounting. Core to the 'successful' integration of sustainability is an understanding that accounting provides 'flawed' measures of performance creating a space for and recognition of legitimate sustainability measures to complement, or even temporarily supersede, the dominant accounting paradigm. We find that differences in individual perceptions of sustainability, within the constraints of past organisational processes, have substantive impact on the extent to which sustainability maybe privileged. Highlights: Tension between accounting and sustainability. Decision making by managers. Sustainability considerations in capital budgeting.